Usability of pulse oximeters used by community health and primary care workers as screening tools for severe illness in children under five in low resource settings: A cross-sectional study in Cambodia, Ethiopia, South Sudan, and Uganda. - Theresa Pfurtscheller; Kevin Baker; Tedila Habte; Kévin Lasmi; Lena Matata; Akasiima Mucunguzi; Jill Nicholson; Anthony Nuwa; Max Petzold; Mónica Posada González; Anteneh Sebsibe; Tobias Alfvén; et al. (Public Library of Science (PLoS), 2023)
Timely recognition and referral of severely ill children is especially critical in low-resource health systems. Pulse-oximeters can improve health outcomes of children by detecting hypoxaemia, a severity indicator of the most common causes of death in children. Cost-effectiveness of pulse-oximeters has been proven in low-income settings. However, evidence on their usability in community health settings is scarce.This study explores the usability of pulse-oximeters for community health and primary care workers in Cambodia, Ethiopia, South Sudan, and Uganda. We collected observational data, through a nine-task checklist, and survey data, using a five-point Likert scale questionnaire, capturing three usability aspects (effectiveness, efficiency, and satisfaction) of single-probe fingertip and multi-probe handheld devices. Effectiveness was determined by checklist completion rates and task completion rates per checklist item. Efficiency was reported as proportion of successful assessments within three attempts. Standardized summated questionnaire scores (min = 0, max = 100) determined health worker's satisfaction. Influencing factors on effectiveness and satisfaction were explored through hypothesis tests between independent groups (device type, cadre of health worker, country). Checklist completion rate was 78.3% [CI 72.6-83.0]. Choosing probes according to child age showed the lowest task completion rate of 68.7% [CI 60.3%-76.0%]. In 95.6% [CI 92.7%-97.4%] of assessments a reading was obtained within three attempts. The median satisfaction score was 95.6 [IQR = 92.2-99.0]. Significantly higher checklist completion rates were observed with single-probe fingertip devices (p<0.001) and children 12-59 months (p<0.001). We found higher satisfaction scores in South Sudan (p<0.001) and satisfaction varied slightly between devices. From a usability perspective single-probe devices for all age groups should be prioritized for scaled implementation. Further research on easy to use and accurate devices for infants is much needed.